2014
DOI: 10.1007/s11259-014-9595-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the green turtle’s leukocyte subpopulations by flow cytometry and evaluation of their phagocytic activity

Abstract: Phagocytosis is a fundamental aspect of innate immunity that is conserved across many species making it a potentially useful health-assessment tool for wildlife. In non-mammalian vertebrates, heterophils, monocytes, macrophages, melanomacrophages, and thrombocytes all have phagocytic properties. Recently, B lymphocytes from fish, amphibians, and aquatic turtles have also showed phagocytic capacity. Phagocytes can be studied by flow cytometry; however, the use of this tool is complicated in reptiles partly beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Importantly, along with these changes, compensatory responses are taking place, thus leading to the observed results. The environmental change shows a great sensitivity with regard to these parameters [31]. In the analyses of white blood cells, a decrease was observed in fish exposed to diclofenac or dexamethasone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, along with these changes, compensatory responses are taking place, thus leading to the observed results. The environmental change shows a great sensitivity with regard to these parameters [31]. In the analyses of white blood cells, a decrease was observed in fish exposed to diclofenac or dexamethasone.…”
mentioning
confidence: 99%
“…The polymorphonuclear cells are the most important leukocytes in fish. The environmental change shows a great sensitivity with regard to these parameters [31]. The lymphocytes are the main defense mechanism in the adaptive immune response in fish; therefore, a decrease in the number of mononuclear leukocytes represents a decrease in one immune response, ultimately predisposing fish to diseases [32].…”
mentioning
confidence: 99%
“…Deviations from normal phagocytic function such as that which might occur with stress [21] can render animals more susceptible to disease [22].…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytosis flow cytometry is a high throughput, quantitative assay, which assesses leukocytes' capacity to phagocytose fluorescently labelled bacteria [25,27]. It has numerous advantages for use in comparative immunology and has proven to be a rapid, reliable tool to evaluate phagocytosis in different species ranging from teleosts [28], mice and macaques [27] to salamanders [29], seals [30], camels [31], sea turtles [22,32], beluga whales [33] and Tasmanian devils [34]. The ex vivo nature of the phagocytosis flow cytometry assay also has advantages over in vivo immunologic tests such as allograft rejection, which may be ethically challenging to carry out in critically endangered species.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade, however, there have been several studies in T. scripta that have given insight into both their adaptive and innate immunity . It has been reported that turtles, including T. scripta, contain populations of B cells with phagocytic potential, not unlike that of the B-1 cell in mammals (Muñoz, Franco-Noguez, Gonzalez-Ballesteros, Negrete-Philippe, & Flores-Romo, 2014;. Given that turtles appear to share some, but not all, immune functions in common with other vertebrates, they provide an interesting group for further study.…”
mentioning
confidence: 99%